PROGRAM KERJASAMA ORANG TUA DENGAN SATUAN PENDIDIKAN ANAK USIA DINI DALAM PEMBERIAN MAKANAN GIZI SEIMBANG DI KOTA PONTIANAK - Suryani, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractParentâ€™s involvement programs are ideas or initiatives organized by schools designed to solicit or encourage parental participation in the education of their children. This research uses descriptive method with qualitative approach. The number of population is 320 (three hundred twenty) units of PAUD as the number of samples are Nine units of PAUD in Pontianak that has received technical guidance of family education. Data collection tools are using interview guides, open questionnaires and documentation. The results of the study were (1) PAUD units in Pontianak already have a balanced nutrition program. (2) PAUD units in Pontianak have implemented parent cooperation program with PAUD unit in providing balanced nutrition food. (3) the implementation of parent cooperative programs with PAUD units in the provision of balanced nutrition food in the first way on PAUD unit creates a comfortable climate; second, communicating earlier in the beginning of the year and third seeking for parent involvement. (4) The impact of parent cooperation program with PAUD unit in first balanced nutrition feeding for early childhood unit is to strengthen the relationship between PAUD unit and parent, secondly for parent that is to build the friendship with other parents and third for early childhood that is to repairing Attitude of children who are difficult to eat. (5) supporting factors are funds and good response from parents to get involved in providing balanced nutrition food. (6) the obstacles are because of limited time for theÂ parents to engage as well as attitudes of parents who are less active..Keywords: Cooperation Program, Balanced Nutrition FoodÂ